FENOMENA MANAJEMEN LABA DAN UNDERPRICING PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING - ANDRE NATA INDRA (Universitas Katolik Widya Mandala Surabaya, 2012)
Recently, companies are often faced with a problem limited funding, which make the company can no longer depend on internal funding sources only. To that, companies must seek external funding sources, which one of them can be done by a public share issue. Public share issue is also known as an IPO (Initial Public Offering). For companies that will perform the IPO, earnings management is a common step that taken to attract investors to invest in that company. Earnings management is management interference in the process of preparing financial statements in order to enhance corporate value. With the earnings management policy, later will happen a phenomenon that called underpricing, where the price of shares traded on the primary market lower than when it is traded on the secondary market.